VO#028 Proposal of shoring pile works at zone C - BUCG-ABC Joint Venture (BUCG-ABC JV) (2023)
This record consists of general correspondence regarding the proposal of shoring pile works at zone C according to specifications, drawings and engineers' instruction for BRACU new campus project.